2022
DOI: 10.1080/10999922.2022.2115235
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review on Perception-Based Definitions and Measurements of Corruption

Abstract: Studies on perceptions of corruption have grown in recent years but are still struggling with several conceptual and measurement issues. This scoping review provides an analysis of the peer-reviewed literature on perception-based corruption. From a total of 1,374 articles surveyed, ninety ultimately met inclusion criteria. We found two main quantifiable trends when exploring our sample: publications in high-impact journals were slow in addressing perception-based corruption, and perceptions of corruption are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 107 publications
0
1
0
Order By: Relevance
“…Two factors come out from this analysis, capturing the two normative theories of political ethics: deontological and consequentialist ethics. 6 A recent scoping review on corruption articles in high-impact journals (Gouvêa Maciel et al, 2022) has also observed that the explicit or implicit definitions of "corruption" discussed in those publications tend to fall into two categories: corruption as a "Deviant Process" (deontological dimension) or as a "Deviant Outcome" (consequentialist dimension). Although there is room for improvement, we believe the selected items are adequate to measure the two conceptual dimensions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two factors come out from this analysis, capturing the two normative theories of political ethics: deontological and consequentialist ethics. 6 A recent scoping review on corruption articles in high-impact journals (Gouvêa Maciel et al, 2022) has also observed that the explicit or implicit definitions of "corruption" discussed in those publications tend to fall into two categories: corruption as a "Deviant Process" (deontological dimension) or as a "Deviant Outcome" (consequentialist dimension). Although there is room for improvement, we believe the selected items are adequate to measure the two conceptual dimensions.…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of the sources of information individuals use to construct their abstract notion of corruption, two criteria are identified in the dedicated literature on perceptions of and attitudes towards corruption (Gouvêa Maciel et al, 2022) as important when people establish of what is or is not corruption: legal rules and standardised expectations guiding the discharge of official duties and responsibilities ( de Sousa, 2008;Gardiner, 1992;Johnston, 1996;Jos, 1993;Kjellberg, 1992); and the positive/negative outcome that derives from those actions or behaviours in office (van Halderen & Kolthoff, 2017). These two dimensions of perceived corruption ('Deviant Process' and 'Deviant Outcome') invoke two opposing normative theories that, cognitively or intuitively, guide individual ethical judgements (Gouvêa Maciel et al, 2022): deontological and consequentialist ethics. Deontology is a rule-based normative ethical theory.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…While it is true that instrumental studies show scales that measure similar variables such as attitudes, perception of corrupt behaviors, and only one evaluates the perception of corruption, there are limited psychometric studies that evaluate the perception that young people have about the perception of corruption in State institutions. its measurement remains a problem (Gouvêa Maciel et al, 2022). Under this problematic context, this research aims to determine the evidence of validity and reliability, and to develop a proposal for percentile norms of a scale on the perception of institutional corruption in university students.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, individuals with major contributions can be unwelcome in environments where mediocrity and/or corruption thrive. Corruption is difficult to measure, but it is probably highly prevalent worldwide [ 2 ]; like any societal structure, research environments may also be affected. In addition, many institutions may be at a loss as to how to appraise impact in a meaningful way.…”
mentioning
confidence: 99%